SYNTHESIS, CHARACTERIZATION, AND EVALUATION OF ANTIMICROBIAL ACTIVITY OF SILVER NANOPARTICLES USING AQUEOUS EXTRACT OF ASPARAGUS RACEMOSUS RHIZOME – AN IN VITRO APPROACH - N, HEMADEVI; P, VENKATALAKSHMI (Asian Journal of Pharmaceutical and Clinical Research, 2020)
Objective: The proposed study is carried out to synthesize and characterize silver nanoparticles (AgNPs) using rhizomes of Asparagus racemosus and to evaluate its antimicrobial activity in vitro. Methods: Aqueous extract of A. racemosus rhizomes was prepared and subjected to preliminary phytochemical screening. AgNPs of A. racemosus rhizomes were prepared using standard procedure. The synthesized particles were characterized using ultraviolet-visible spectrophotometry, Fourier transform infrared (FTIR) spectroscopy, and scanning electron microscopic (SEM) analysis. Further, these nanoparticles were subjected to in vitro antimicrobial studies. Results: Preliminary phytochemical analysis showed the presence of tannins, phlobatannins, saponins, flavonoids, terpenoids, triterpenoids, alkaloids, carbohydrates, proteins, anthraquinones, polyphenols, and glycosides. The study of synthesized AgNPs showed a sharp absorbance at 410 nm. The results of FTIR analysis confirmed the presence of phenol, alkanes, aliphatic amine, secondary alcohol, alkenes, and aromatic amines. SEM analysis of the AgNPs revealed higher density polydispersed AgNPs of various sizes. The AgNPs synthesized from rhizome extract showed higher toxicity toward tested microorganisms when compared to extract alone. Conclusion: It has been concluded that silver nanoparticles of A. racemosus could be a good source of plant-derived antimicrobials.